Analysis of the Role of Educational Supervision in Enhancing Teacher Professionalism - Novianti; Sophia Tri satyawati; Wahyudi (Journal of Studies in Academic, Humanities, Research, and Innovation, 2024)
This study aims to analyze the role of educational supervision in enhancing teacher professionalism at SMK Karmel Tangerang Banten. The approach used in this research is qualitative, with data collection techniques through interviews, observations, and documentation studies. The results of the study show that educational supervision at SMK Karmel has a significant impact on improving teachers' pedagogical, social, and personality competencies. Through supervision carried out by the principal and supervisors, teachers receive constructive feedback that allows them to develop teaching skills, improve communication and collaboration with colleagues, and foster professional attitudes in carrying out their duties. Additionally, supervision based on teacher development and empowerment also plays a crucial role in enhancing teachers' motivation and confidence. However, the study also identifies some challenges in the implementation of supervision, such as limited time and teachers' discomfort with evaluative approaches that focus too much on weaknesses. Overall, educational supervision conducted with a collaborative and supportive approach plays an important role in improving teacher professionalism at SMK Karmel. This study contributes to the development of supervision policies in vocational high schools to enhance the quality of education.